Integration of Personality, Visionary Leadership, Organizational Culture, and Service Quality to Build Organizational Image - Radnawati, Daisy; Hermawan, Andi (Dinasti Publisher, 2026)
An image is one of the important assets for an organization that should be continuously built and maintained. A good image is one of the important tools, not only to attract consumers in choosing products or services, but also to improve customer satisfaction attitudes towards the organization. The image also shows the existence of an organization in the public eye, namely, showing the public's view of the organization that has formed over a long period of time. A well-formed image will also have a good impact on achieving the goals set by individuals or organizations. Based on preliminary research, it is known that the Image of PGRI Schools in Bogor Regency is relatively suboptimal. Therefore, research is needed to obtain information on variables related to improving Service Quality. The purpose of this study is to implement strategies and methods to improve organizational image by conducting research on the influence of personality variables, visionary leadership, organizational culture, and service quality. This study uses the path analysis method to determine the influence between the variables studied and the SITOREM method for indicator analysis to obtain optimal solutions in efforts to improve organizational image.